Reconciling architectural education and environmental psychology - Moulay, Amine; Ujang, Norsidah (Common Ground Research Networks, 2020)
One of the primary outcomes of the latest United Nations conference on housing and sustainable development is that architectural practice should transcend the limits of aesthetics and functionality restricted to physical and social attributes. The new United Nations' urban agenda for the next two decades is to provide responsive and inclusive urban infrastructures for cities. However, the architectural practice in education does not integrate into the design process the psychological dimensions embedded in the environmental psychology field. Fewer efforts are directed to the value of place attachment considered a significant aspect of environmental psychology. This is due to the multidimensional, multi-paradigmatic, and multidisciplinary approaches regarding the concept of place attachment. Hence, this review article addresses the value of environmental psychology to prominence in the field of architecture and summarizes the latest conceptualizations of place attachment, then proposes an integrated framework for responsive design. This review provides further insight into the fundamental value of reconciling environment psychology with architectural practice to encourage a holistic approach, underpin innovative concepts, and bring an added value to the architectural education in the Gulf Cooperation Council States (GCC) region.